Parliamentary Systems in Continental European Countries and its Relationship to the Effectiveness of Legislative Institutions - Rohmah, Elva Imeldatur; Huroirah, Ernawati; Putra Prasetya, Jean Arya (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
Every country has a unique style regarding the parliamentary system they follow. This parliamentary system may experience changes or developments that differ from the initial concept. It is expected because each country has other political, cultural, social, and economic conditions. It is normative legal research with a historical and conceptual approach, then conducted in a comparative study. The results of this study found that the French parliamentary system is included in the category of Medium-Strength bicameralism with asymmetrical and incongruent characteristics. The Dutch parliament belongs to medium-strength bicameralism with symmetrical and harmonious features. The Austrian legislature, known as the Bundesrat, does not have the same power as the Nationalrat, so the management of the two chambers of parliament is asymmetrical. Meanwhile, the parliamentary system in Indonesia can be classified as medium-strength bicameralism with asymmetrical and incongruent buildings. The parliamentary system can indirectly affect the effectiveness of the legislature's performance. Sometimes, the system adopted can make parliament an effective and efficient institution or vice versa. A small example is France, which can complete over 50% of proposed legislation in one year. Meanwhile, from 2020-2024, only 17 draft laws were constructed in Indonesia out of 215 registered. This figure is only 7.9% of the total proposed bill. Suppose the parliamentary system adopted has yet to bring parliament into a better, transparent, efficient, and open legislative body. In that case, the system can be re-evaluated by considering the existing ideal parliamentary concept.